2017
DOI: 10.3390/w9070465
|View full text |Cite
|
Sign up to set email alerts
|

Early Warning and Forecasting System of Water Quality Safety for Drinking Water Source Areas in Three Gorges Reservoir Area, China

Abstract: Nowadays, the effects of water pollution accidents on water quality safety and regional residents' living have attracted worldwide attention. Therefore, the objective of this research is to propose an early warning and forecasting model and develop a visual system of water quality safety for drinking water source areas in the Three Gorges Reservoir Area under accident conditions. Based on an Instantaneous Point Source Two-dimensional Water Quality Model and the security requirements of water quality, an early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…There are many metagenomic researches done on polluted water sample to identify the bacterial contamination (Ding et al 2017; Saleem et al 2018; Samson et al 2019; Behera et al 2020). This study of metagenomic sequencing of water sample from Yamuna River revealed different organisms for the evaluation of microbial diversity and abundance.…”
Section: Discussionmentioning
confidence: 99%
“…There are many metagenomic researches done on polluted water sample to identify the bacterial contamination (Ding et al 2017; Saleem et al 2018; Samson et al 2019; Behera et al 2020). This study of metagenomic sequencing of water sample from Yamuna River revealed different organisms for the evaluation of microbial diversity and abundance.…”
Section: Discussionmentioning
confidence: 99%
“…The establishment of a global environmental monitoring system called ''early warning'' was introduced in the environmental field (Yuan, 1987). Nevertheless, most related studies were concentrated on the forecasting of floods (Plate, 2008), early warning of water shortage and water resource carrying status (Yu et al, 2020;Shi and Zhang, 2021), and prediction of water quality and pollutant (Ding et al, 2017;Jin et al, 2019;Imani et al, 2021), whereas very few paid attention to the comprehensive early warning of the water environmental system risk. Although the WECC does not have a uniform definition, it is a broad concept related to the environmental properties of water, and it focuses on the mechanisms of interaction in human (socioeconomic)-water environmental systems (Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, monitoring and detecting warning signs of changes in drinking water quality variables play an essential role in ensuring high-quality drinking water and avoiding health-related problems [18]. Many methods, such as data mining [19], instantaneous point source two-dimensional water quality modeling [20], the driving force-pressure-state-influence-response (DPSIR) model [21], the entropy-weight method [22], and the system dynamics (SD) model [23], have been used to predict temporal and spatial variability and trends and to model average pollutant concentration levels and peak values in primary urban drinking water sources.…”
Section: Introductionmentioning
confidence: 99%